A 5-Year Analysis of Physician-Industry Interactions, Physician Gender, and Anti-VEGF Use in US Ophthalmologists: Short Title: Physician-Industry Interactions and Anti-VEGF Use. (17th November 2021) - Watane, Arjun; Kalavar, Meghana; Patel, Marissa; Yannuzzi, Nicolas; Vanner, Elizabeth A.; Kuriyan, Ajay E.; Sridhar, Jayanth
ABSTRACT: Purpose : To explore physician gender, industry payments, and prescribing habits of anti-vascular endothelial growth factor (VEGF) agents. Methods : Retrospective review of U.S. ophthalmologists prescribing and receiving industry payments for aflibercept and/or ranibizumab (brand anti-VEGF injections) between August 2013 to December 2017. Results : Men receiving industry payments were older and had longer post-residency experience than women (both P < .001). Men were more likely to receive industry payments ( P = .01), receive >5 payments ( P = .003), and receive payments totaling >$1000 ( P = .008). Men administered more injections on average than women when receiving >3 industry payments ( P < .001) or when receiving >$100 ( P < .01). On multivariate analysis, years in practice, male gender, number of payments, and total value of payments were independent factors associated with the number of brand injections administered (all P < .001). Conclusions : A positive association between industry payments and brand anti-VEGF use was identified, however, causality was not determined. Gender bias may be present in physician-industry relationships.